Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Audio Visual untuk Meningkatkan Kemampuan Berpikir Kritis Anak Sekolah Dasar - Ahmad Yani; Nuril Huda; Haerussaleh (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model supported by audio-visual media in improving critical thinking skills of elementary school students in science subjects. The research was conducted at SDN Kalinganyar, Sumenep, using a quantitative experimental method with a saturated sampling technique involving fifth-grade students. Data collection was performed through tests and observation sheets, followed by statistical analysis using SPSS. The results show a significant improvement in critical thinking skills in the experimental class compared to the control class. The posttest average score of the experimental group reached 84.27, significantly higher than the control group’s average of 70.60. Hypothesis testing using an independent sample t-test revealed a significance value of 0.000 (<0.05), indicating that the PBL model combined with audio-visual media has a statistically significant impact on students’ critical thinking abilities. The use of visual media enhances student engagement, motivation, and understanding by providing contextual and multisensory learning experiences. This research concludes that integrating PBL with audio-visual support is an innovative and effective strategy for developing 21st-century learning skills, particularly in fostering critical thinking among elementary students.